Mahogany (Swietenia mahagoni) Leaf Extract Exhibits Strong Antibacterial Activity Against Enterococcus faecalis: A Promising Natural Alternative to Chlorhexidine for Root Canal Infections - Firdha Muharraran; Mangatas H P Hutagalung; Ariska Putri Siregar (HM Publisher, 2025)
Enterococcus faecalis is a prevalent bacterium in root canal infections, exhibiting high resistance to conventional antibacterial agents. Mahogany (Swietenia mahagoni) leaf extract, rich in flavonoids, saponins, and tannins, has demonstrated promising antibacterial properties. This study investigated the antibacterial efficacy of mahogany leaf extract against E. faecalis and compared its effectiveness to chlorhexidine, a commonly used root canal irrigant. A laboratory experimental study was conducted using the disk diffusion method on Mueller Hinton Agar (MHA). Mahogany leaf extract was prepared at concentrations of 25%, 50%, and 70%. Chlorhexidine (0.2%) served as the positive control, and dimethyl sulfoxide (DMSO) as the negative control. The diameter of inhibition zones was measured after 24 hours of incubation. Statistical analysis was performed using One-Way ANOVA and Post Hoc LSD tests. All concentrations of mahogany leaf extract exhibited significant antibacterial activity against E. faecalis (p < 0.05). The 70% concentration produced the largest inhibition zone (20.39 ± 1.38 mm), followed by 50% (18.67 ± 1.12 mm) and 25% (17.28 ± 0.60 mm). The inhibition zones of the 50% and 70% mahogany leaf extract were comparable to those of chlorhexidine (19.40 ± 0.70 mm). In conclusion, mahogany leaf extract demonstrates strong antibacterial activity against E. faecalis, suggesting its potential as a natural alternative to chlorhexidine for root canal infections. Further research is warranted to explore its clinical application in endodontic treatment.